Diseño de un sistema de control interno contable para la cooperativa de transportes loja - Morocho Moreta, Kelly Thalía (2020)
The thesis entitled "DESIGN OF A CONTAINING INTERNAL CONTROL SYSTEM FOR LOJA TRANSPORT COOPERATIVE" was developed with the aim of designing internal control policies and procedures, which help to maintain a logical and sequential order of the activities carried out in the cooperative, which will provide a useful tool for them to have timely control, reliable and complete of the operations carried out in it. The design of the internal control system made it possible to achieve the specific objectives set out in the thesis project. For the internal control diagnosis, a questionnaire with objective questions was applied to the five control components for the staff of the administrative and accounting departments, which was assessed on the basis of the rating matrix of the level of trust and control risks, thus demonstrating that there is no adequate internal control, causing deficiencies that are detrimental to the cooperative. After a thorough review of regulations, laws, regulations and resolutions issued by the regulators, policies and procedures were established for the proper functioning of the activities in order to carry out the operations in an orderly and coordinated manner, which shall enable staff to discharge their responsibilities truthfully and accurately at the time of reporting accounting and financial information. 5 The internal control system was developed, which includes the components of the control environment, risk assessment, control, information and communication activities, monitoring and monitoring, and their respective flow diagrams; this design will allow the manager and staff to have adequate control of the various risks, safeguard assets and reliability and integrity of financial and managerial information through appropriate and timely decision-making. It is concluded that the design of the internal control system constitutes an information tool on the policies and procedures essential to provide reasonable assurance that the objectives will be achieved, therefore it is recommended that they be used to improve control processes and to allow managers adequate control to achieve reliability, timeliness, security and confidentiality of information processed to ensure the orderly and efficient conduct of the entity.